Changing trend in prevalence of refractive errors: a hospital-based study - Rajput, Vimal Krishna; Shetty, Naren B. (International Journal Of Community Medicine And Public Health, 2020)
Background: Refractive errors are the second most common reason of blindness in India after cataract. It accounts for 33.3% of cases of childhood blindness. The purpose of this study was to estimate the prevalence of refractive error and related visual impairment in children visiting a tertiary care eye center in Southern India. Methods: This was hospital-based descriptive study. Children <15 years of age with significant refractive error were included in the study. They were examined for visual acuity measurements, ocular motility evaluation, retinoscopy and autorefraction under cycloplegia, and examination of the anterior segment and fundus. Significant refractive error was defined as myopia ≥-0.75D, hypermetropia >+2D and astigmatism >0.75D. Descriptive statistics with frequency, mean±Standard deviation were computed for better and the worse eye. Statistical tests were applied between the worse and better eye using Chi square test. Results: A total of 946 children were screened. The mean age was 10.5±6.2 years (3-15 years) with 503 (53.2%) males and 443 (46.8%) females. With respect to vision in the worse eye; 54.01% (n=511) had moderately subnormal vision. One hundred and twenty- two children (23.4%) of <10 years, and 351 (67.4%) of ≥10 years group had myopia, with statistically significant difference (p<0.001). The reverse pattern was seen with respect to hypermetropia and astigmatism. Prevalence of amblyopia was found to be 8.6%. Conclusions: Though myopia is more prevalent among general population, prevalence of astigmatism is higher among children attending an eye hospital and uncorrected astigmatism is the most significant amblyogenic factor in refractive amblyopia.